Association of sleep quality and body mass index (BMI) with metabolic syndrome risk factors among medical students - Yuliana; Callista, Aurelia; Astiarani, Yunisa; Pramono, Laurentius Aswin; Lilis; Mariani Santosa (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Sleep quality reflects an individual’s satisfaction with the sleep process, which is essential for cognitive, psychological, metabolic, and cardiovascular health. Poor sleep quality is prevalent among medical students and may elevate their risk of metabolic syndrome. This study investigated the association between sleep quality and body mass index (BMI) with metabolic syndrome risk factors in medical students. This was a cross-sectional study involving 98 first- to third-year preclinical medical students. Sleep quality was assessed by using the Pittsburgh sleep quality index (PSQI) questionnaire, BMI was measured from body weight and height, and metabolic syndrome risk factors were evaluated through waist circumference, blood pressure, fasting blood glucose, and high-density lipoprotein (HDL) cholesterol levels. Data was analyzed using Chi square and Fisher’s exact test. Results showed that 54.08% of students had good sleep quality and 42.86% had a normal BMI. However, 59.18% of students exhibited at least one metabolic syndrome risk factor, including central obesity (51.02%), hypertension (20.41%), dyslipidemia (13.27%), and high fasting blood glucose (1.02%). There was no association between sleep quality and metabolic syndrome risk factors. The BMI showed no association with fasting blood glucose and HDL cholesterol level. However, BMI showed a significant association with waist circumference (p<0.001) and blood pressure (p = 0.005). These findings emphasize the importance of addressing the MBI in mitigating metabolic syndrome risks among medical students.